Anne of green gables - Montgomery, L. M. (Lucy Maud), 1874-1942 ([Boston, Mass] : Thomson Heinle, 2007)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her
Title from container
Keywords: English literature; Orphans -- Juvenile fiction; Teachers -- Juvenile fiction; Friendship -- Juvenile fiction; Country life -- Prince Edward Island -- Juvenile fiction